Integrated use of phosphorus, farmyard manure and biofertilizer improves the yield and phosphorus uptake of black gram in silt loam soil. - Jagdish Singh; Rajan Bhatt; Dhaliwal S S; B S Dhillon; Asma A Al-Huqail; Alanoud Alfagham; Manzer H Siddiqui; Hayssam M Ali; Faheema Khan; Ritesh Kumar (PLoS ONE, 2022)
An experiment on the use of farmyard manure and biofertilizer along with application of chemical phosphorus was conducted to assess the impact of differential doses of phosphorus, farmyard manure and consortium biofertilizer application on the development, yield and phosphorus uptake during the year 2018 and 2019. The impact of different treatments was recorded on the plant height, dry matter partition, yield and yield attributes, phosphorus uptake and soil phosphorus availability using standard methods. The data revealed significant improvement in yield, yield attributes, phosphorus uptake and soil phosphorus availability. The integration of farmyard manure and biofertilizer with 60 kg ha-1 SSP (single superphosphate) has improved the black gram yield by 7.4% and 3.28% respectively over the use of 60 SSP alone. The phosphorus uptake in black gram with application of Farm yard manure and biofertilizer along with 60 kg ha-1 SSP has improved the uptake by 7.18% and 2.51% respectively over the use of 60 kg ha-1 SSP alone. The results highlight the need of integrated application of farm yard manure, biofertilizer for sustainable production of black gram in the region.